Investigation of the Epidemiology of Small Ruminant Lentivirus Infections southeast part of the Marmara region of Turkey - Sait, A; Ince, OB (Journal of the Hellenic Veterinary Medical Society, 2023)
Small ruminant lentiviruses (SRLVs) are viral pathogens that are common in goats and sheep, affect production, and cause significant economic losses in small ruminant breeding. Caprine arthritis encephalitis virus (CAEV) and Maedi-Visna virus (MVV) are prototypes of SRLVs. Both of them affect animal health and welfare in sheep and goats and cause progressive and persistent infections in the small ruminant industry. The present study aimed to reveal the epidemiological status of lentivirus infection in the sheep region in Yalova province located in the southeast part of the Marmara region and determine the circulating genotypes by conducting the sequence analysis of the samples detected positive by a molecular method and molecular characterization of the detected field strains. To that end, 231 sheep blood samples were used between May 2016 and April 2018. Based on sampling results of the PCR test and ELISA tests, 5.62% (13/231) and 5.19% (12/231) positivity rates were found in sheep, respectively. According to the ELISA test results, a significant difference was found in terms of age groups (6 months -1 age, 1-3 age, >3 age) (χ2: 6.01; p=0.04). Furthermore, the sequence analysis of the gag gene region detected the existence of the A genotype of small ruminant lentiviruses in sheep. The data obtained from the study revealed a low seroprevalence course of SRLV infection in the study area in the absence of a systematic disease control program.